(untitled) (Jurnal Sistem Informasi Akuntansi, 2022)
The increasing level of need for information systems and information technology requires Government Agencies to keep up with the times. The need for a system is definitely very necessary, because to make a successful program run, it is necessary to have a system that supports and makes the government agency more advanced. So far, the recording of goods in the Infrastructure and Transportation. Development Division of DISHUB Singkawang still uses physical documents and is not neatly arranged and reports are also stored in Microsoft Excel applications which are stored separately, when you need the report it takes a long time to find the data. Therefore, the author will design a web-based inventory system whose purpose is to facilitate inventory management. In this study, the data collection method used by the author is observation, interviews, and literature study and uses the waterfall method as a software development method used by the author. From this research, the authors hope that by making an inventory system at DISHUB Singkawang, it will make it easier for goods managers to input goods, process inventory, process goods transactions, and report goods data.